The formation of the conception of the aesthete education by die means of theatrical art tn pedagogical theory in XIX-XX cen. - M.A. Derhach (Academy of Cognitive and Natural Sciences, 2006)
In the article are depicted conceptual positions of pedagogues in the end of the XIX - the beginning of XX cen. that become the basically resources of aesthete development of individual child education.